Pengaruh Influencer Social Media Dan Citra Merek Terhadap Niat Beli Pada Generasi Z - Ni Luh Komang Elistya Putri Damayanti; I. G. A. Agung Omika Dewi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Gen Z students are known to be easily influenced by influencers and brand image in making purchasing decisions, especially for beauty products like Jennskin. This study aims to determine the influence of social media influencers and brand image on Generation Z purchase intentions, specifically for the local e-commerce brand Jennskin, which actively utilizes digital marketing strategies for Generation Z consumers at the National University of Education, Denpasar. The sampling method used in this study was purposive sampling, resulting in a sample of 120 undergraduate students from the National University of Education, Denpasar, belonging to Generation Z who purchased Jennskin products on the Jennskin e-commerce platform. Data were collected using a questionnaire, and the analysis technique used was multiple linear regression analysis using SPSS version 26. Based on the analysis, this study shows that social media influencers have a partial positive and significant effect on purchase intentions among Generation Z. Brand image has a partial positive and significant effect on purchase intention among Generation Z. Social media influencers and brand image simultaneously have a positive and significant effect on purchase intention among Generation Z.